(untitled) (Research, Society and Development, 2021)
The northeast of Brazil stands out for having a high prevalence of visceral leishmaniasis (VL), being indicated as the main endemic region of Brazil. This fact makes epidemiological studies in the region of great value, as they help to design more assertive public health policies for the control of VL. In this context, this research aims to outline the epidemiological profile of VL between 2007 and 2019 and outline a profile of vulnerability to the disease in the state of Bahia. This is a sectional, exploratory, descriptive, quantitative and retrospective study. The data used related to VL cases in the state of Bahia come from the SINAN database (Information System and Notifiable Diseases). Data analysis was performed using the GraphPad Prism program. Bahia represents the third state with the highest number of notified VL cases in northeastern Brazil between 2007 and 2019, with a total of 4,156 notified cases. A spatial analysis of this distribution demonstrates that Juazeiro (146 cases) and Guanambi (125 cases) are the municipalities in Bahia with the highest number of reported cases in the period evaluated. Through a stratified analysis of the data, we observed a greater vulnerability among males, browns, with a low level of education and aged 1-4 years. With this work, we reinforce the endemic character of visceral leishmaniasis in the state of Bahia and the need to adopt public health policies aimed at combating VL.